Antiplatelet medications in acute coronary syndromes and percutaneous coronary interventions: focus on tirofiban - T. A. Batyraliev; D. V. Preobrazhensky; D. V. Fetzer; B. A. Sidorenko; S. A. Pataraya (Кардиоваскулярная терапия и профилактика)
The review presents literature data on the key role of platelet aggregation (PA) for intracoronary thrombogenesis in various acute coronary syndromes (ACS) and percutaneous coronary interventions (PCI). Clinical pharmacology of main antiplatelet medication (APM) classes is discussed, with emphasis on a new APM class - blockers (inhibitors) of IIb/IIIa glycoprotein receptors (GP IIb/IIIa). The authors analyse the results of randomized clinical trials on effectiveness and safety of abciximab, tirofiban, and eptifibatide in non-ST ACS and planned or urgent PCI. Clinical situations and other factors determining the choice of specific GP IIb/IIIa blocker are discussed.